Fatal Idiopathic Hyperammonemia after Induction Chemotherapy for Acute Myeloid Leukemia - Christophe Angelo; Marie-Françoise Vincent; Mina Komuta; Philippe Hantson; Nicole Straetmans; Edwige Boulet (Case Reports in Hematology)
Idiopathic hyperammonemia is a rare but potentially fatal complication occurring in patients with acute leukemia or bone marrow transplantation. The role of some specific anticancer drugs may be discussed, but the etiology of hyperammonemia is often multifactorial. We report the case of a 40-year-old woman who developed fatal idiopathic hyperammonemia two weeks after induction chemotherapy with idarubicin-aracytine for acute myeloid leukemia. Despite intensive care management and extrarenal epuration, the patient was declared brain dead two days after hyperammonemia onset.